Pelatihan Daring Pemrograman Python di SMAN 58 Jakarta - Nur Hayati; F Fauziah; Novi Dian Nathasia; Harun Al Jafar; Hanni Oktaviana; Laurensius Oliver J.S; Adelia Putri H (Jurnal TUNAS, 2023)
The Python programming language is included in one of the languages that is easy to learn and implement in various fields such as games, website applications, software development, mathematical simulations to scripting systems. So that not only companies, but academics also use python programming to complete research such as robotics, economics, machine learning, data science, data mining, deep learning to scientific computing. Based on this, the target for this service is python programming training for class X students of SMAN 58 Jakarta. Target training is given to high school participants with the aim of changing the image of youth that learning to program is not difficult and to provide a stimulant of comfort when they learn programming. In this training, Jupiter Notebook or Google Collabs software is used which can be accessed online without the need to install. This training is carried out online due to the condition of schools that are still implementing PPKM. The results of the training show that students can understand the basics of the Python programming language which can be seen from the results of the exercises that can be completed by most of the training participants.school. In this training, Jupiter Notebook software is used if it is adequate or can use google collabs online without the need to install. In the training,